Pengaruh Profitabolitas, Likuiditas, Leverage, dan Ukuran Perusahaan terhadap Pengungkapan CSR di Perusahaan Subsektor Makanan dan Minuman yang terdaftar di BEI periode 2017-2019 - Sauh Hwee Teng; Ananta Cahyani; Sonya Olivia Isabella; Fahira Elsyamila Aisyah (Owner : Riset dan Jurnal Akuntansi, 2022)
This research was conducted because it aims to find out how (1) the effect of profitability on CSR. (2) the effect of liquidity on CSR. (3) the influence of Leverage on CSR. (4) and the effect of firm size on CSR. The population that we study is the Food and Beverage Subsector Companies that are listed on the Indonesia Stock Exchange (IDX) in 2017-2019. In taking the sample using the purposive sampling method and obtaining 30 companies with the number to be observed 48. This study usesmethod. a quantitative approachbecause the data of this research is in the form of numbers and analyzed using statistics and is causal. From the results of this study are: (1)Profitability is proven to have a negative and insignificant effect on CSR. (2) Liquidity has a positive and insignificant effect on CSR. (3) Leverage is also proven to have a positive and insignificant effect on CSR. (4) and firm size proved to have a negative and insignificant effect on CSR. These results indicate that the Liquidity and Leverage variables can affect CSR and vice versa, the profitability and company size variables have no effect on CSR.